2019
DOI: 10.1136/bmjopen-2018-027962
|View full text |Cite
|
Sign up to set email alerts
|

Are Australians ready for warning labels, marketing bans and sugary drink taxes? Two cross-sectional surveys measuring support for policy responses to sugar-sweetened beverages

Abstract: ObjectiveTo assess public support for 10 potential policy initiatives to reduce sugar-sweetened beverage (SSB) consumption.DesignA 2014 historical data set, which employed a face-to-face survey in one Australian state (study 1), provided the basis for comparison with our 2017 nationally representative, cross-sectional, computer-assisted telephone interviewing population survey (study 2).ParticipantsStudy 1: South Australians, 15+ years (n=2732); study 2: Australians, 18+ years (n=3430).Primary outcome measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(97 citation statements)
references
References 69 publications
11
82
4
Order By: Relevance
“…In total, 3430 participants were recruited into the study (participation rate = 44%). The sample is described in detail and compared to national population data elsewhere [23]. Briefly, 49% were female, mean age was 46.9 (Standard Deviation [SD] = 18.3) years, and the demographic profile (in terms of sex, age, and employment status) of respondents was consistent with the national population data [54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 3430 participants were recruited into the study (participation rate = 44%). The sample is described in detail and compared to national population data elsewhere [23]. Briefly, 49% were female, mean age was 46.9 (Standard Deviation [SD] = 18.3) years, and the demographic profile (in terms of sex, age, and employment status) of respondents was consistent with the national population data [54].…”
Section: Resultsmentioning
confidence: 99%
“…In Australia, like many countries, policy action is slow and legislative reform is conspicuously absent. This is despite strong and increasing consumer support for intervention [23], and comprehensive evidence-based guidelines for action [24].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 38% held a bachelor degree or higher, which was higher than the national average (26%) [51]. Further demographic characteristics of the sample are available elsewhere [45,46]. Most respondents could report sugar intake guidelines consistent with WHO recommendations: 74% indicated that the adult guideline for teaspoons of sugar was between 0 and 5, 20% indicated that it was between 6 and 12 and 3% indicated it was 13 or more (4% indicated that they did not know).…”
Section: Resultsmentioning
confidence: 99%
“…This study was conducted on data from a large Australian study on SSB consumption (methods reported in detail in [46]). A national computer-assisted telephone survey of adults aged 18 years and over was conducted between February and April 2017.…”
Section: Methodsmentioning
confidence: 99%
“…This is also supported by the studies of Bollard et al ., Miller et al ., Roberto et al ., and Donnelly et al . [ 15 32 33 34 ] The pictorial warning was found to have more impact than sole textual warning and discouraged people to buy SSBs, which stresses the importance of pictorial warnings on the packaging. [ 9 33 35 36 ]…”
Section: Discussionmentioning
confidence: 99%